Social organization for improved system management and sustainable irrigated agriculture in small dams: an action research program. Final report - Starkloff, R.; Bandaragoda, Don Jayatissa; Cheema, M.A.; Bhatti, M.A. (International Water Management Institute. Pakistan National Program, 1999)
The final report of this project documents the lessons learned by researchers, social organizers, agency personnel and farmers. The project has demonstrated the willingness and ability of farmers and agency personnel to manage the land and water resources of the area jointly. The view of the researchers is that the small dams offer an excellent opportunity for the promotion of reforms in the irrigation sector.